Relative treatment effects of first-line chemotherapy and immunotherapy for hepatocellular carcinoma: A systematic review and meta-analysis - Bahirwani, Janak; Jai Kumar Ahuja, Suruchi; Changela, Madhav; Patel, Het; Patel, Nishit; Kaneriya, Maulik; Patel, Vishal (Cancer pathogenesis and therapy, 2025)
Hepatocellular carcinoma (HCC) is the most common primary liver malignancy and the fourth most common cause of cancer-related mortality worldwide. Despite advances in immunotherapies and targeted treatments for HCC, chemotherapy remains a valuable first-line treatment. However, the efficacy of immunotherapy compared to that of chemotherapy is unknown. This study aimed to provide a comprehensive understanding of the effects of chemotherapy and immunotherapy on survival outcomes, response rates, and adverse effects. A thorough literature search of multiple electronic databases, including MEDLINE (PubMed), Embase, Web of Science, Cochrane Central Register of Controlled Trials, and ClinicalTrials.gov was conducted from database inception to February 2024 to identify randomized controlled trials (RCTs) that compared first-line chemotherapy (doxorubicin, cisplatin, tislelizumab, sorafenib, and fluorouracil) with immunotherapy (pembrolizumab and nivolumab) for advanced HCC. Two reviewers independently identified the studies, obtained relevant information, and assessed the possibility of bias. The hazard ratios (HR) for progression-free survival (PFS) and overall survival (OS) were merged using random effects meta-analysis. Twenty studies with 1183 patients were examined. All studies had a high risk of bias. According to a meta-analysis, immunotherapy was linked to a significantly better PFS than chemotherapy (HR: 1.44, 95% confidence interval [CI] 1.04–2.00, I2 = 32%). OS showed a similar trend, although the difference was not statistically significant (HR: 1.26, 95% CI 0.96–1.66, I2 = 0%). Sensitivity analysis revealed that immunotherapy continued to improve PFS compared to chemotherapy while having no discernible effect on OS. First-line immunotherapy may offer PFS advantages over chemotherapy for the treatment of advanced HCC. However, a high risk of bias limits definitive conclusions. Larger, higher-quality RCTs are needed to confirm the potential benefits of OS and minimize bias. Although chemotherapy remains the mainstay of treatment in regions with limited access, the widespread availability of immunotherapy makes it essential to compare both treatments to determine the most appropriate first-line option for advanced HCC. [Display omitted] •Evidence is lacking for hepatocellular carcinoma (HCC) treatment regarding optimal chemotherapy vs. immunotherapy subgroups.•Information on the impact of combination strategies on therapy outcomes is limited.•First-line immunotherapy may offer progression-free survival advantages over chemotherapy in advanced HCC.•Larger and higher-quality randomized controlled trials (RCTs) are necessary to confirm potential overall survival advantages.